A Critical View of the Current Use of Electromyographic Biofeedback in General Relaxation Training - Wilkinson, Margaret (Canadian Journal of Counselling and Psychotherapy, 2012)
General relaxation training is frequently used in the treatment of psychological and psychosomatic disorders. Recently, the application of EMG (electromyographic) feedback to general relaxation training has generated enthusiasm among clinicians. As currently used in general relaxation training, EMG feedback relaxation training is limited to the frontalis (forehead) muscle. However, there is little empirical evidence to support the assumption that the effects of such training generalize to other muscle groups. Further research on the extent of the effects of frontalis EMG feedback relaxation training is required, and an investigation of alternative ways of using EMG feedback to facilitate general relaxation appears necessary.